Wildlife forensic DNA and lowland tapir (Tapirus terrestris) poaching - Sanches, A. [UNESP]; Perez, W. A. M.; Figueiredo, M. G.; Rossini, B. C.; Cervini, M.; Galetti, P. M.; Galetti, Mauro [UNESP] (Springer, 2011)
DNA molecular analyses were used in a forensic investigation involving illegal wildlife poaching in central Brazil. The Brazilian environmental agency (IBAMA) sent us two samples of confiscated meat from illegal poaching for species and individual identification. Comparative analysis of cytochrome b sequences (1,070 bp) provided incontestable evidence that the meat samples were from the lowland tapir, Tapirus terrestris. The analysis of nine microsatellites indicated that the two seized meat samples shared the same genotypes, implying that meat from only one individual was present. The lowland tapir is the last representative of megamammals in South America and is a vulnerable species, locally extinct in several regions. The present paper reports a successful genetic investigation of an illegal hunting crime, in which DNA- based molecular analyses of seized ground meat samples were the only tool able to identify the species and individual, proving to be highly useful for wildlife crime investigations.
Keywords: Forensic genetics; Species identification; Hunting; Cytochrome b; Microsatellite